ANEMIA OF CHRONIC DISEASE: FEATURES OF PATHOGENESIS AND POSSIBLE THERAPEUTIC CORRECTION (LITERATURE REVIEW AND RESULTS OF OWN RESEARCH) - V. Т. Sakhin; Е. R. Madzhanova; E. V. Kryukov; S. P. Kazakov; O. A. Rukavitsin (Онкогематология, 2018)
The review contains data on new important aspects of the pathogenesis and treatment of anemia of chronic diseases. The complex multicomponent genesis of this anemia is shown, which is based on the disturbances in iron metabolism, damage of proliferation and differentiation of erythropoiesis cells, a decrease in the synthesis and biological activity of erythropoietin. The value of blood transfusions, iron preparations and erythropoiesis-stimulating agents in the treatment of patients with anemia of chronic diseases is shown. It is established that the safety data of these methods are quite contradictory, further studies are needed in this direction with the aim of developing uniform principles for the diagnosis and treatment of this anemia. Comparative analysis results of interleukin-6 (IL-6), interleukin-10 (IL-10) and tumor necrosis factor alpha (TNF-α) concentration in patients with malignant neoplasms with anemia and without it are presented, as well as correlation analysis for evaluation their influence on the number of erythrocytes and hemoglobin concentration. Sixty three patients with stage II–IV disease were examined. In patients with anemia, compared with the control group, higher levels of IL-6 (41.5 (3.8–31.1) and 7.1 (0.00–9.40) pg/ml), TNF-α (58.6 (36.1–81.1) and 8.25 (1.3–13.6) pg/ml) and IL-10 (18.3 (4.5–14.4) and 0.9 (0.3–5.5) pg/ml) were revealed (p <0.05). For IL-6, there was a correlation with erythrocytes (r = –0.55), hemoglobin (r = –0.52); for TNF-α, a correlation with erythrocytes (r = –0.74), hemoglobin (r = –0.69) was revealed; for IL-10, there was a correlation with hemoglobin (r = –0.74) and erythrocytes (r = –0.6). The results confirm the importance of these cytokines in the genesis of anemia in cancer patients.